2019
DOI: 10.1051/e3sconf/20199704032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of punching shear mechanism of reinforcing concrete slab

Abstract: The analysis of various regulatory methods for calculating reinforced concrete slabs for pushing and comparing with experiment results is made. The tested sample, measuring equipment and test bench are described. Sizes and materials for experimental prototype were chosen by existing beamless and capless slabs of monolithic reinforced concrete superstructures with column grid from 8×8 to 9×9 m. Experimental research results of reinforcing concrete plate structure are presented for study purpose of stress-strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Analyzing previously performed works [1][2][3][4][5][6][7][8], the following types of rigid capitals can be distinguished (it is understood not to strengthen the punching zone with reinforcement, but to introduce elements into the system that significantly increase the rigidity of the support section) In the course of the conducted research, a specific task was set -to solve the issue of punching. At the same time, the issue of the rigidity of this section, with the exception of individual works, has not been fully investigated (a number of authors carried out movement control and concluded that there was a significant increase in the rigidity of the zone at the column).…”
Section: The Status Of the Issue Of Strengthening The Punching Zonementioning
confidence: 99%
“…Analyzing previously performed works [1][2][3][4][5][6][7][8], the following types of rigid capitals can be distinguished (it is understood not to strengthen the punching zone with reinforcement, but to introduce elements into the system that significantly increase the rigidity of the support section) In the course of the conducted research, a specific task was set -to solve the issue of punching. At the same time, the issue of the rigidity of this section, with the exception of individual works, has not been fully investigated (a number of authors carried out movement control and concluded that there was a significant increase in the rigidity of the zone at the column).…”
Section: The Status Of the Issue Of Strengthening The Punching Zonementioning
confidence: 99%
“…Moreover, higher reinforcement ratios led to improved punching-shear capabilities, reduced reinforcement strains, and smaller slab deflections . Further research has explored punching tests for bidirectional slabs (Trekin and Pekin., 2019), accompanied by the formulation of accurate punching capacity calculation sequences. A puncture resistance formula, considering the bending reinforcement ratio, demonstrated reasonable agreement with experimental data (Guo and Cheng., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the calculated punching strength using this equation to test data, a small average error is obtained. Trekin and Pekin [7] presented punching tests for two-way slabs. They also formulated a sequence for calculating the punching capacity which proved to be accurate.…”
Section: Introductionmentioning
confidence: 99%